Two new species of Amphinemura (Plecoptera: Nemouridae) from the Gaoligong Mountains of Yunnan, China - Li, Weihai; Wang, Ying; Yang, Ding (Zootaxa, 2016)
Two new species of the nemourid genus Amphinemura, A. apicilobata sp. nov. and A. bimaculata sp. nov. are described from the Gaoligong Mountains of Yunnan Province, China. The new species are compared with related congeners.